Effect of functionalized trititanate nanotubes on the properties of crosslinked cationic polymer nanocomposite. Issue 9 (6th February 2015) - Villenas, Iván; Rivas, Bernabé L; Torres, Cecilia; Campos, Cristian; Urbano, Bruno F
Abstract The synthesis and characterization of a crosslinked polymer nanocomposite containing titanium oxide nanotubes as filler are presented. First, the TiO2 nanotubes were synthesized using a hydrothermal procedure and further functionalized using the organosilane reagent γ‐methacryloxypropyltrimethoxysilane. Subsequently, the modified nanotubes were incorporated into a polymer matrix using in situ polymerization of a mixture of monomer, crosslinker and initiator. Diverse characterization techniques were used at different stages of the synthesis, including transmission (TEM) and scanning electron microscopies, X‐ray diffraction (XRD), solid‐state 29Si NMR and 13C NMR spectroscopy and nitrogen adsorption isotherms at 77 K. The as‐synthesized nanotubes correspond to the trititanate phase verified using XRD, and their presence within the nanocomposite was confirmed using TEM analysis. In addition, TiO2 particles were detected on the surface of the nanocomposite. The nanocomposite exhibited a slight increase of Vickers microhardness while the water absorption decreased with oxide content attributed to trititanate nanotubes acting as multifunctional crosslinker.© 2015 Society of Chemical Industry